Variable vacuum honeycomb-felt thermal insulation material and its preparation method and application
Patent Information
- Application Number
- CN202610875484.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-23
AI Technical Summary
现有技术多采用主动控制系统(如风扇、电加热)或简单的两态保温结构,存在能耗高、结构复杂、响应不连续等问题
1.本发明的核心在于,当外界温度低于0℃时,相变材料凝固、SMPU模量升高,微阀关闭,蜂窝芯维持高真空态,实现极致保温;当外界温度高于0℃后,相变材料融化、SMPU软化收缩,微阀随温度升高线性开启,外界空气渐进式渗入,真空度降低,散热能力线性增强。整个过程完全被动,无需外部能源,实现了材料热阻随环境气温的智能、连续、自适应调节,特别适用于65-90℃热源在宽温域环境下的高效热管理。
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention belongs to the field of intelligent thermal insulation materials technology, specifically relating to a variable vacuum honeycomb felt thermal insulation material, its preparation method, and its application. Background Technology
[0002] The strategic importance of high-efficiency thermal insulation materials in building energy conservation, industrial insulation, aerospace, and cold chain transportation is becoming increasingly prominent. Traditional thermal insulation materials mainly include two categories: organic foamed materials (such as EPS, XPS, and polyurethane foam) and inorganic fiber / porous materials (such as rock wool, glass wool, aluminum silicate, and aerogel). Although they have achieved large-scale application, both face insurmountable performance bottlenecks. While organic thermal insulation materials are lightweight and have a low thermal conductivity (approximately 0.03-0.04 W / (m²),... While rock wool and glass wool have good high-temperature resistance and are typically used at temperatures below 100℃, they are prone to shrinkage, melting, and even combustion at high temperatures, posing serious safety hazards. They also lack aging and weather resistance, have short service lives, and easily cause environmental pollution after disposal. Inorganic materials, although resistant to high temperatures and flame retardant, generally suffer from high thermal conductivity, brittleness, poor impact resistance, and susceptibility to moisture absorption. For example, the thermal conductivity of rock wool and glass wool can increase by 20%-30% after absorbing moisture, drastically reducing their insulation performance. Aluminum silicate fiber is prone to pulverization and has a limited service life. Aerogel, although with a thermal conductivity as low as 0.012-0.02 W / (m²), is also problematic. However, its high cost, poor mechanical properties, and susceptibility to cracking greatly limit its widespread application.
[0003] Vacuum insulation panels (VIPs), as a new generation of high-efficiency insulation materials, eliminate gas convection heat transfer by sealing the core material within a high-barrier membrane and creating a vacuum, reducing the thermal conductivity to 0.005 W / (m²). Below K), the insulation efficiency is 5-8 times that of traditional materials, and it has been gradually applied in low-temperature cold chain, medical insulated boxes, high-end buildings and other scenarios. However, the core defects of existing vacuum insulation panels are significant: First, the core material is mostly powder, short fiber or open-cell foam, with loose structure, low mechanical strength, poor compressive and shear resistance, and easy to collapse under external pressure, resulting in vacuum failure and a sharp drop in insulation performance; Second, the vacuum chamber is an integral sealed structure, and the vacuum degree cannot be adjusted. Once a part is damaged, the whole thing is scrapped and cannot be repaired and reused, and it is difficult to adapt to the insulation requirements of complex curved surfaces and irregularly shaped components; Third, although traditional honeycomb structure vacuum materials improve structural strength through honeycomb core, the honeycomb channels are mostly connected or semi-closed, with poor vacuum retention. They are prone to air leakage after long-term use and cannot achieve dynamic control of vacuum degree, making it difficult to meet the variable insulation requirements under different temperature and pressure conditions; Fourth, existing products are mostly rigid boards with poor flexibility, inconvenient transportation and installation, and cannot adapt to complex working conditions such as vibration and impact, thus limiting application scenarios.
[0004] Chinese invention patent application CN116811398A discloses a polyurethane composite board based on phase change insulation and its manufacturing method, including a first panel and a second panel, with a phase change polyurethane insulation layer disposed between the first panel and the second panel. The phase change polyurethane insulation layer has a honeycomb porous structure. The phase change polyurethane insulation layer is formed by mixing a phase change composite material and a polyurethane foaming material at a mass ratio of 1:2 and then foaming them. The phase change composite material is a third-order phase change composite material, which is composed of one or more of tetradecane, octadecane, paraffin wax, and graphene aerogel.
[0005] Another Chinese invention patent application, CN113524802A, discloses a low thermal conductivity phase change energy storage insulation board, its preparation method, and its application. It discloses a core board structure and a multifunctional skin structure covering the surface of the core board structure. The multifunctional skin structure encapsulates a phase change material. The core board structure includes a uniformly porous material as a reinforcing material and a thermal insulation foam material. The thermal insulation foam material is distributed and filled within the uniformly porous material… The thermal insulation foam material includes any one or a combination of two or more of polyurethane foam, polystyrene foam, and melamine foam; and / or, the uniformly porous material has a honeycomb structure, preferably including any one of aluminum honeycomb, aramid paper honeycomb, and resin-impregnated glass fiber fabric honeycomb. In this low thermal conductivity phase change energy storage insulation board, the phase change material filled inside the skin layer absorbs and stores a large amount of heat during the heating process and slowly releases it during the heat release process. By combining it with low thermal conductivity foam material, the thermal insulation performance of the phase change energy storage insulation board can be greatly improved. This solves the problem that the thermal insulation performance of the composite board will decrease after the phase change material is introduced into the insulation board system, so that the composite board can achieve adaptive temperature regulation while ensuring thermal insulation capacity.
[0006] While the above materials offer some improvements in thermal insulation performance, some shortcomings remain. For thermal equipment, pipelines, or battery systems operating in a constant temperature range (e.g., 65-90℃), thermal management faces a dilemma: extreme insulation is needed in low-temperature environments to reduce heat loss and prevent freezing; while enhanced heat dissipation is required in high-temperature environments to prevent overheating. Existing technologies often employ active control systems (such as fans or electric heating) or simple two-state insulation structures, which suffer from high energy consumption, complex structures, and discontinuous response. Therefore, there is an urgent need for a smart insulation material that can adapt to external climate changes without requiring external energy consumption and offers superior performance. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a variable vacuum honeycomb felt insulation material that adapts to ambient temperature, its preparation method, and its application.
[0008] Terminology Explanation: Unless otherwise defined, all technical terms in this document have the same meanings as commonly understood by one of ordinary skill in the art to which the subject matter of the claims pertains. Unless otherwise stated, all patents, patent inventions, and publications cited in this document are incorporated herein by reference in their entirety. If multiple definitions exist for terms in this document, the definitions in this chapter shall prevail.
[0009] It should be understood that the above brief description and the following detailed description are exemplary and for illustrative purposes only, and do not limit the subject matter of the invention in any way. In this invention, the singular is used in conjunction with the plural unless otherwise specifically stated. It should also be noted that, unless otherwise stated, the use of “or” or “or” means “and / or”. Furthermore, the use of the term “comprising” and other forms such as “including,” “containing,” and “contains” are not limiting.
[0010] Unless specifically defined herein, the use of all commercially available products herein employs standard techniques. For example, it may be carried out using the manufacturer's instructions for use with the kit, or in accordance with methods known in the art or the description of this invention. The techniques and methods described herein can generally be implemented according to conventional methods well known in the art, based on the descriptions in the various summary and more specific documents cited and discussed in this specification.
[0011] The terms “optional / arbitrary” or “optionally / arbitrarily” mean that the event or situation described below may or may not occur, including both the occurrence and non-occurrence of the event or situation.
[0012] The term "variable vacuum honeycomb felt insulation material" used in this article refers to a functional material that utilizes the absorption or release of latent heat during phase transitions to regulate temperature. It can store or release heat energy through solid-liquid and solid-solid phase transitions while maintaining a relatively constant temperature, acting as a "heat bank." These materials are typically integrated into building walls, roofs, or floors to effectively mitigate indoor temperature fluctuations, improve comfort, and reduce air conditioning and heating energy consumption. For example, during the day when temperatures rise, the material melts and absorbs heat, slowing the rise in room temperature; at night when temperatures drop, the material solidifies and releases heat, mitigating the decrease in room temperature.
[0013] The term "protective / weathering layer" used in this article refers to a functional barrier designed to protect materials or structures from environmental erosion. It is widely used in fields such as construction, industry, electronics, and transportation. Its core function is to resist long-term damage from natural factors such as ultraviolet rays, moisture, oxygen, salt spray, and temperature changes, thereby extending the life of the substrate and maintaining its performance stability.
[0014] The term "infrared transparent spacer" used in this article refers to a functional structural layer specifically designed to improve the efficiency of heat conduction and diffusion. It is widely used in electronic equipment, buildings, aerospace and industrial systems. Its core function is to quickly and evenly dissipate the heat generated by the heat source, prevent local overheating, ensure stable equipment operation or improve energy utilization efficiency.
[0015] The term "thermochromic-radiative layer" used in this article refers to a type of intelligent functional layer that can autonomously adjust its optical and thermal radiation properties according to changes in ambient temperature. It is widely used in building energy conservation, thermal management coatings, and smart windows, with the core objective of achieving an adaptive temperature control effect that provides warmth in winter and coolness in summer. These materials dynamically adjust the solar reflectivity (visible-near-infrared band) and the infrared emissivity of the atmospheric window (8–13 μm) through a temperature response mechanism. At high temperatures, they enhance reflection and radiative cooling; at low temperatures, they reduce reflection and absorb solar energy to assist heating, thereby significantly reducing building cooling and heating energy consumption.
[0016] To achieve the objectives of this invention, the following technical solution is adopted: On the one hand, the present invention provides a variable vacuum honeycomb felt insulation material, characterized in that the following are stacked sequentially from the side away from the heat source to the side close to the heat source: a protective / weather-resistant layer, an infrared transparent spacer layer, a thermochromic-radiation layer, a variable vacuum honeycomb core and an inner surface sealing layer; The variable vacuum honeycomb core is composed of multiple honeycomb cells, and the inner surface of the honeycomb cells is sequentially covered with a high infrared reflective layer and a composite material; the raw materials of the composite material include phase change material microcapsules with glass transition temperatures of -5 to 5℃ and shape memory polyurethane prepolymer. On the upper and lower end faces of the honeycomb cells, a PET / Al composite valve membrane with micro-valve distribution is adhered.
[0017] This invention employs a multi-layered composite flexible felt material, the core of which is a "variable vacuum honeycomb core". The innermost layer of the honeycomb core's pore walls is coated with a composite material formed from phase change material (PCM) microcapsules and shape memory polyurethane (SMPU), with the phase change point of the PCM and the glass transition temperature (Tg) of the SMPU precisely set near 0°C. The honeycomb is covered with valve membranes equipped with "micro-valve" on both the top and bottom.
[0018] When the ambient temperature (Ta) is below 0°C, the PCM solidifies, and the SMPU remains in a glassy state with high modulus and a fixed shape, forcibly closing the microvalve. At this time, the honeycomb core maintains the factory-preset high vacuum state, resulting in extremely low thermal conductivity and achieving optimal insulation. When Ta is above 0°C, the PCM melts and absorbs heat, and the SMPU transforms into a highly elastic state, with a sharp drop in modulus and a tendency to revert to its contracted state after being "frozen and shaped." This contraction causes the microvalve to open. The higher the Ta, the more thoroughly the PCM melts, the greater the SMPU contraction force, and the larger the microvalve opening. More external air enters the honeycomb under the pressure difference, gradually losing vacuum. The overall equivalent thermal conductivity and infrared emissivity of the material increase linearly, and the heat dissipation capacity increases linearly accordingly. In some specific embodiments of the present invention, the phase change material microcapsules are n-hexadecane microcapsules with a phase change point of 0°C. In some specific embodiments of the present invention, the mass percentage of the phase change material microcapsules in the composite material is 30-50%.
[0019] In some specific embodiments of the present invention, the phase change material microcapsules are eutectic phase change materials of n-pentadecane / n-heptadecane with a phase change point of -5℃ to 5℃.
[0020] In some specific embodiments of the present invention, the mass ratio of n-pentadecane to n-heptadecane is 55-65:35-45; In some specific embodiments of the present invention, the n-hexadecane microcapsules are purchased from the MIS series phase change materials of Hangzhou Luer New Material Technology Co., Ltd., with a phase change point of 0°C, a latent heat of about 220 J / g, and a solid powder appearance. The organic phase change material is fixed in the support material using porous adsorption technology and then encapsulated in microcapsules.
[0021] In some specific embodiments of the present invention, the preparation method of the eutectic phase change material of n-pentadecane / n-heptadecane includes mixing n-pentadecane with a purity of 99% or higher and n-heptadecane with a purity of 99% or higher at a mass ratio of 55:45, melting and stirring in a 50°C water bath for 30 min, and naturally cooling to obtain a eutectic with a phase change point of -5°C. In some specific embodiments of the present invention, the preparation method of the n-pentadecane / n-heptadecane eutectic phase change material includes mixing n-pentadecane with a purity of 99% or higher and n-heptadecane with a purity of 99% or higher at a mass ratio of 65:35 to obtain a eutectic with a phase change point of 5°C.
[0022] In some specific embodiments of the present invention, the preparation method of the shape memory polyurethane prepolymer includes: dehydrating polycaprolactone diol under vacuum at 100°C for 2 hours, cooling the temperature to 75-85°C, and then adding 4,4-diol. ,- Diphenylmethane diisocyanate, with a molar ratio of isocyanate groups to hydroxyl groups of 1.05, reacts at 75-85℃ for 1-3 hours, then 1,4-butanediol is added, stirred for 1-5 minutes, vacuum degassing for 2-10 minutes, and poured into a preheated mold. It is first cured at 55-65℃ for 10-15 hours, and then vulcanized at room temperature for 4-8 days to synthesize the product.
[0023] Preferably, the method for preparing the shape memory polyurethane prepolymer includes: vacuum dehydrating polycaprolactone diol at 100°C for 2 hours, cooling it to 80°C, and then adding 4,4-diol. , Diphenylmethane diisocyanate (MDI) with an R value (-NCO / -OH) controlled at 1.05 was reacted at 80℃ for 2 hours. Then, the chain extender 1,4-butanediol (BDO) was added, and the mixture was stirred rapidly for 2 minutes. After vacuum degassing for 5 minutes, the mixture was poured into a preheated mold and first cured at 60℃ for 12 hours. Then, it was synthesized under the following conditions: after curing at room temperature for 7 days, the product was obtained.
[0024] In some specific embodiments of the present invention, the honeycomb holes are regular hexagons; In some specific embodiments of the present invention, the preparation of the honeycomb cells includes: using aramid-mica paper, impregnating it with 20wt% phenolic resin, curing it at 170-190℃ for 1-5 minutes to make prepreg paper; molding and folding the prepreg paper into a regular hexagonal honeycomb core blank with a side length of 3-5mm and a height of 9-11mm to obtain the honeycomb core blank.
[0025] In some specific embodiments of the present invention, the microvalve is a cross-shaped microslit formed by laser ablation on a PET / Al composite valve membrane, wherein the arm length of the microslit is 20-40µm and the dot spacing is 0.5-0.9mm.
[0026] In some specific embodiments of the present invention, the high infrared reflectance layer is a vacuum sputtered aluminum layer with a thickness of 70-90 nm and an infrared reflectance ≥94%.
[0027] In some specific embodiments of the present invention, the preparation of the variable vacuum honeycomb core includes the following steps: S1: Vacuum sputtering aluminum layer on the inner surface of the honeycomb hole wall is used as a high infrared reflective layer; S2: Mix phase change material microcapsules with shape memory polyurethane prepolymer to prepare composite coating slurry. Apply the composite coating slurry to the high infrared reflective layer by scraping method, and dry and cure to obtain honeycomb core. S3: Laser processing of a cross-shaped micro-valve on the valve diaphragm; S4: The valve diaphragm with micro-valve is hot-pressed and bonded to the upper and lower end faces of the honeycomb core obtained in step S2 to obtain a variable vacuum honeycomb core.
[0028] In some specific embodiments of the present invention, in S2, the coating amount on one side is 23-27 g / m2, the drying temperature is 75-90℃, and the drying time is 1-5 min; In some specific embodiments of the present invention, in S3, a heat-sealing adhesive is pre-coated on one side of the valve membrane, and a CO2 laser with a power of 8-12W and a pulse width of 0.1-0.3ms is used to ablate the PET / Al film to form a cross-shaped micro-slit array.
[0029] In some specific embodiments of the present invention, in S4, the hot pressing is performed at 120-140°C and 0.4-0.6MPa pressure for 0.5-2s.
[0030] In some specific embodiments of the present invention, the protective / weather-resistant layer is a PET film with a thickness of 40-60µm.
[0031] In some specific embodiments of the present invention, the infrared transparent spacer layer is a porous polyethylene film with an average pore size of 4-6µm, a porosity of 60%, and a thickness of 90-110µm.
[0032] In some specific embodiments of the present invention, the thermochromic-radiation layer is a 20-40µm composite coating, and the raw materials of the composite coating include vanadium dioxide composite microcapsules and methylated melamine-formaldehyde resin in a mass ratio of 1:2-4. The preparation of the vanadium dioxide composite microcapsules includes: (1) Vanadium dioxide nanoparticles were dispersed in an ethanol solution containing silane coupling agent KH-570 and stirred at 55-65℃ for 3-5h to modify the surface, thereby obtaining modified vanadium dioxide. (2) Mix melamine and formaldehyde solution at a molar ratio of 1:2-4, adjust the pH to 8-9 with triethanolamine, and react at 65-75℃ for 20-40 min to obtain melamine resin prepolymer; (3) Disperse the modified vanadium dioxide in deionized water and sonicate for 20-40 min to obtain a vanadium dioxide dispersion; slowly add the melamine resin prepolymer to the vanadium dioxide dispersion, adjust the pH to 4-5 with citric acid, stir at 65-75℃ for 2 h, filter, wash and dry to obtain vanadium dioxide composite microcapsules. The composite coating is prepared by mixing vanadium dioxide composite microcapsules with methylated melamine-formaldehyde resin at a mass ratio of 1:3, adding an appropriate amount of deionized water and grinding and dispersing for 30 minutes, then adding 1-2% of the mass of MF resin as a blocked p-toluenesulfonic acid curing agent, stirring evenly, and coating it onto a PE film. It is then pre-cured at 80°C for 30 minutes and then cured at 120°C for 30 minutes to obtain the final product. Preferably, the preparation of the vanadium dioxide composite microcapsules includes: dispersing VO2 nanopowder with a phase change temperature of 68°C in an ethanol solution containing silane coupling agent KH-570, and stirring at 60°C for 4 hours for surface modification; mixing melamine and formaldehyde solution at a molar ratio of 1:3, adjusting the pH to 8-9 with triethanolamine, and reacting at 70°C for 30 minutes to obtain a melamine resin prepolymer; dispersing the modified VO2 in deionized water and sonicating for 30 minutes; slowly adding the prepolymer to the VO2 dispersion, adjusting the pH to 4-5 with citric acid, stirring at 70°C for 2 hours, filtering, washing, and drying to obtain VO2-MF composite microcapsules; Preferably, the composite coating is prepared by mixing the above-mentioned vanadium dioxide composite microcapsules with methylated melamine-formaldehyde resin at a mass ratio of 1:3, adding an appropriate amount of deionized water and grinding and dispersing for 30 minutes, then adding 1-2% of the mass of MF resin as a blocked p-toluenesulfonic acid curing agent, stirring evenly, and coating it onto a PE film. It is then pre-cured at 80°C for 30 minutes and then cured at 120°C for 30 minutes to obtain the final product.
[0033] In some specific embodiments of the present invention, the inner surface sealing layer is a 22-27µm thick high-temperature resistant silicone.
[0034] In some specific embodiments of the present invention, the thermal insulation material is provided with circumferential elastic bands around its perimeter. The circumferential elastic bands are woven from PET and spandex, with a mass ratio of PET to spandex of 80-90:10-20, preferably 85:15. By adjusting the weaving density and binding pre-tension rate of the bands, the applied radial pre-tightening pressure is controlled within the range of 1-10 kPa.
[0035] On the other hand, the present invention provides a method for preparing the aforementioned variable vacuum honeycomb felt insulation material, comprising the following steps: (1) The protective / weather-resistant layer, infrared transparent spacer layer, and thermochromic-radiation layer are stacked on the side of the variable vacuum honeycomb core away from the heat source in sequence. The inner surface sealing layer is attached to the side of the variable vacuum honeycomb core close to the heat source to obtain the laminated material. The laminated material is heat-sealed around its perimeter, and an air extraction port is reserved to obtain the overall component. (2) Heat the entire assembly to 110-130°C, evacuate through the air extraction port until the internal air pressure is below 100Pa, and seal the air extraction port under vacuum. (3) Cool the entire assembly after sealing the air extraction port to a temperature of -15~-5℃ and set for 20-50 minutes; (4) The circumferential elastic band is tied around the periphery to obtain the product.
[0036] Preferably, in step (1), the perimeter of the laminated material is heat-sealed with a 4-6 mm wide PET / Al composite foil, and a φ2-4 mm air extraction port is reserved. Preferably, in step (2), the extraction port is melted and sealed with heat-sealing pliers while maintaining a vacuum.
[0037] Thirdly, the present invention provides an application of the variable vacuum honeycomb felt insulation material described above or the variable vacuum honeycomb felt insulation material prepared by the preparation method described above in 60-90℃ heat source equipment, special functional clothing, 60-120℃ industrial low temperature steam pipelines, building exterior wall insulation systems in severely cold regions, cold chain transportation equipment, new energy battery thermal management, or solar water heater collector tube insulation.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The core of this invention lies in the fact that when the ambient temperature is below 0°C, the phase change material solidifies, the SMPU modulus increases, the microvalve closes, and the honeycomb core maintains a high vacuum state, achieving ultimate heat preservation. When the ambient temperature is above 0°C, the phase change material melts, the SMPU softens and shrinks, the microvalve opens linearly with the temperature increase, ambient air gradually infiltrates, the vacuum level decreases, and the heat dissipation capacity increases linearly. The entire process is completely passive, requiring no external energy source, and achieves intelligent, continuous, and adaptive adjustment of the material's thermal resistance according to the ambient temperature. It is particularly suitable for efficient thermal management of heat sources with temperatures ranging from 65-90°C in a wide temperature range environment.
[0039] 2. No external power consumption required and fully passive intelligence: This invention relies entirely on the material's own physical properties to respond to ambient temperature, without the need for sensors, controllers, or external energy sources.
[0040] 2. Continuous linear adjustment: The thermal resistance of the insulation material of this invention decreases smoothly and linearly as the ambient temperature rises, rather than a simple "on / off" two-state switch, making temperature control more precise and efficient.
[0041] 3. Adaptive to climate: The thermal insulation material of this invention uses 0℃ as the natural switching point, perfectly matching the winter and summer climate boundaries of most regions, achieving "winter insulation and summer dissipation".
[0042] 4. Compact structure and maintainable: The insulation material of this invention is thin and has low surface density, can be flexibly wrapped, has a reserved vacuum replenishment interface, and has a long service life.
[0043] 5. Wide range of applications: This invention can be directly applied to fields requiring adaptive thermal management, such as electrolytic cells, process pipelines, and energy storage battery packs. Detailed Implementation
[0044] The present invention will be further described below with reference to specific embodiments. All materials used in the present invention are commercially available conventional materials. Among them, Aramid-mica paper: purchased from Hubei Ping An Electric Yunshui ® Aramid fiber mica paper.
[0045] Hexadecane microcapsules: purchased from Hangzhou Luer New Material Technology Co., Ltd., MIS series phase change material, phase change point 0℃, latent heat of about 220J / g, appearance is solid powder, organic phase change material is fixed in support material by porous adsorption technology and microencapsulated.
[0046] Shape memory polyurethane prepolymer (SMPU prepolymer): Polycaprolactone diol with a molecular weight of 2000 was vacuum dehydrated at 100°C for 2 hours, cooled to 80°C, and 4,4-diol was added. , - Diphenylmethane diisocyanate, with R value (-NCO / -OH) controlled at 1.05, reacted at 80℃ for 2h to obtain a prepolymer; added chain extender 1,4-butanediol, stirred rapidly for 2min, vacuum degassed for 5min, poured into a preheated mold, cured at 60℃ for 12h, and then vulcanized at room temperature for 7 days to obtain SMPU with Tg of 0℃.
[0047] PET / Al film: purchased from TOPPAN Co., Ltd., model GL-ARH, PET thickness 6µm / Al thickness 6µm, single-sided pre-coated with EVA heat sealant.
[0048] Fluorinated PET film: Purchased from Dongguan Youlun Electronic Materials Technology Co., Ltd., PET fluorine release film, thickness 50µm.
[0049] Porous PE membrane: Purchased from Asahi Kasei Corporation, model Sunmap TM LC-T, thickness 100µm, porosity 60%, average pore size 5µm.
[0050] VO2-MF coating: Melamine-formaldehyde resin (MF) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., with a solid content of approximately 60%, and the curing agent was p-toluenesulfonic acid.
[0051] Preparation of vanadium dioxide composite microcapsules: VO2 nanoparticles with a phase change temperature of 68℃ were dispersed in an ethanol solution containing silane coupling agent KH-570 and stirred at 60℃ for 4 hours for surface modification; melamine and formaldehyde solutions were mixed at a molar ratio of 1:3, and the pH was adjusted to 8-9 with triethanolamine, and reacted at 70℃ for 30 minutes to obtain melamine resin prepolymer; modified VO2 was dispersed in deionized water and ultrasonically treated for 30 minutes; the prepolymer was slowly added to the VO2 dispersion, the pH was adjusted to 4-5 with citric acid, stirred at 70℃ for 2 hours, filtered, washed, and dried to obtain the final product.
[0052] Preparation of composite coating: The above VO2 composite microcapsules were mixed with methylated melamine-formaldehyde resin (purchased from Shanghai Maclean Biochemical Technology Co., Ltd.) at a mass ratio of 1:3. An appropriate amount of deionized water was added and the mixture was ground and dispersed for 30 min. Then, 1.5% of the mass of MF resin and a blocked p-toluenesulfonic acid curing agent were added. After stirring evenly, the mixture was coated onto a PE film. The film was pre-cured at 80℃ for 30 min and then cured at 120℃ for 30 min to obtain the final product.
[0053] High-temperature resistant silicone film: purchased from Hangzhou Guige New Material Technology Co., Ltd., BD-KYN series fully transparent silicone precision film, 25µm thick.
[0054] PET-spandex woven elastic straps: purchased from Yick Fat Trading Co., Ltd., with a PET to spandex mass ratio of 85:15. The applied radial pre-tension pressure is controlled within the range of 1-10 kPa by adjusting the weaving density and binding pre-stretch rate of the straps.
[0055] Eutectic phase change material of n-pentadecane / n-heptadecane: Mix n-pentadecane with 99% purity and n-heptadecane with 99% purity at a mass ratio of 55:45, melt and stir in a 50℃ water bath for 30 minutes, and cool naturally to obtain a eutectic with a phase change point of -5℃; mix at a mass ratio of 65:35 to obtain a eutectic with a phase change point of 5℃.
[0056] Graphene nanosheets: purchased from Changzhou Sixth Element Materials Technology Co., Ltd., model SE1233, number of layers <10, sheet diameter 5-10µm.
[0057] Example 1 This embodiment provides a zero-power variable vacuum honeycomb felt insulation material for 75℃ hot water pipes.
[0058] 1. Material Structure and Preparation (1) Fabrication of variable vacuum honeycomb core: Using 120g / m 2 Aramid-mica paper is impregnated with 20wt% phenolic resin and cured at 180°C for 3 minutes to produce prepreg paper.
[0059] The prepreg paper is molded and folded into a regular hexagonal honeycomb core blank with a side length of 4mm and a height of 10mm.
[0060] An infrared reflective layer (reflectivity ≥ 94%) is formed by depositing a pure aluminum film of about 80 nm thickness on the inner surface of all the pore walls of the honeycomb core blank through vacuum sputtering.
[0061] Preparation of phase change-SMPU coating slurry: Mix n-hexadecane microcapsules (40wt%) with SMPU prepolymer evenly.
[0062] The above slurry was applied to the aluminum film on the honeycomb cell wall using a scraping method, with a coating amount of approximately 25 g / m² on one side. 2 It is dried in an 80℃ oven for 2 minutes to solidify and form a composite pore wall.
[0063] (2) Preparation of microvalve membrane: A 12µm thick PET / Al film is selected, and a 2µm thick heat-sealing adhesive is pre-coated on one side.
[0064] A 10W CO2 laser with a pulse width of 0.2ms was used to ablate the PET film, forming a cross-shaped microslit array with slit arms of 30µm, a dot spacing of 0.7mm, and an areal density of approximately 2×10⁴ cm⁻¹. -2 .
[0065] (3) Overall packaging and vacuum shaping: The aforementioned micro-valve membrane is placed over the upper and lower end faces of the honeycomb core and then hot-pressed at 130°C and 0.5MPa for 1 second to firmly bond the valve membrane to the honeycomb end face while ensuring unobstructed micro-slits.
[0066] A 50µm thick fluorinated PET film, a 100µm thick porous PE film, and a 30µm thick VO2-MF coating coated on the PE film are stacked sequentially on the side of the honeycomb core away from the heat source.
[0067] A 25µm thick high-temperature resistant silicone film is bonded to the side of the honeycomb core closest to the heat source.
[0068] Use a 5mm wide PET / Al composite foil to heat-seal all the above-mentioned laminated materials around the edges to form a sealed "bag", and leave a φ3mm air extraction nozzle.
[0069] Place the entire "bag" in a 120°C oven and connect a vacuum pump through an air extraction nozzle to evacuate the air until the internal pressure is below 100Pa.
[0070] While maintaining a vacuum, use heat-sealing pliers to melt and seal the extraction port.
[0071] Immediately transfer the sealed component to an environment of -10°C for cooling and shaping for 30 minutes. During this process, the SMPU is "frozen" in its contracted state, permanently memorizing the shape under this high vacuum.
[0072] After cooling, an elastic strap woven from PET-spandex is wrapped around the material to provide a circumferential preload of approximately 5 kPa.
[0073] 2. Working principle and performance The material used is a flexible rolled felt approximately 10.2 mm thick. It is then wrapped around a water pipe at 75°C. When the ambient temperature Ta = -20℃: hexadecane is solid, SMPU is rigid, and the micro-valve is completely closed. A negative pressure of approximately 300 Pa is maintained inside the honeycomb structure, resulting in an overall thermal conductivity as low as 0.038 W / (m·K), a heat flux density of only 23 W / m², and a surface temperature of approximately 2℃, with no risk of condensation.
[0074] When the ambient temperature Ta rises to 0-5℃: hexadecane begins to melt and enter the phase transition plateau, the SMPU modulus drops sharply and begins to shrink, and the micro-valve is partially opened. Air enters, the internal pressure of the honeycomb rises to about 3 kPa, and the heat dissipation capacity begins to increase.
[0075] When the ambient temperature Ta=10℃: the phase transition ends, the SMPU softens fully, and the microvalve opening is larger. The internal air pressure of the cell is about 50kPa, the heat flux density increases to 52W / m2, and the heat dissipation capacity is about 2.3 times higher than that at -20℃.
[0076] When the ambient temperature Ta=25℃: the SMPU is in a fully elastic state, the micro-valve is fully open, and natural convection is enhanced. The internal air pressure of the honeycomb is close to atmospheric pressure, the heat flux density reaches 72W / m2, and the heat dissipation capacity is about 3.1 times higher than that at -20℃, effectively preventing water pipes from overheating in summer.
[0077] 3. Maintenance If the performance deteriorates after long-term use, the material can be re-vacuumed at 80°C for 5 minutes using the matching portable vacuum nozzle to restore its performance.
[0078] Example 2 This embodiment is basically the same as Embodiment 1, except that: the n-hexadecane microcapsules are replaced with a eutectic phase change material of n-pentadecane / n-heptadecane, and its phase change point can be adjusted to -5℃ or 5℃. The rest is the same as in Embodiment 1.
[0079] Example 3 This embodiment is basically the same as Embodiment 1, except that 1 wt% of graphene nanosheets are incorporated into the SMPU prepolymer. The resulting composite SMPU has a certain degree of conductivity. When manual intervention or program control is required, a low-voltage DC current can be applied to the material, and Joule heating is used to actively heat and shrink the SMPU, thereby forcibly opening the microvalve to enhance heat dissipation and achieving a dual-parameter "electric-thermal" control mode.
[0080] Compare with Example 1 This comparative example uses a high-efficiency vacuum insulation panel (VIP) from the Supertech-VAP series purchased from Fujian Saite New Materials Co., Ltd., with a thermal conductivity of 0.002 W / (m·K), and a Wanefoam panel purchased from Wanhua Energy Saving Technology Group Co., Ltd. ® RCB series, with rigid polyurethane foam (PUR) with a thermal conductivity of 0.024 W / (m·K) as the control sample.
[0081] Compare with Example 2 The difference between this comparative example and Example 1 is that the phase change microcapsules are different; they are n-octadecane microcapsules, purchased from Shanghai Rushang New Energy Technology Co., Ltd., model MPCM5. Since the phase change point is much higher than 0°C, the microcapsules solidify at low temperatures, causing the SMPU segments to be rigidly bound. The microvalve is still difficult to close completely at low temperatures (such as -20°C), and the low-temperature insulation performance is inferior to that of Example 1.
[0082] Compare with Example 3 The difference between this comparative example and Example 1 lies in the preparation method of the SMPU prepolymer. Specifically, the R value (-NCO / -OH) during the synthesis process was adjusted to 0.95. The resulting SMPU exhibited a lower degree of crosslinking, and its glass transition temperature (Tg) drifted from 0°C to -15°C. This led to a significant decrease in modulus at -5°C, premature opening of the microvalve, and deterioration of its low-temperature insulation performance.
[0083] Compare with Example 4 The difference between this comparative example and Example 1 is that no phase change material microcapsules were added; only pure SMPU was used as the coating. Due to the lack of solid-solid phase change latent heat support from the phase change material, the SMPU's temperature response sensitivity is reduced, the linearity of the microvalve opening is poor, and at low temperatures, due to the lack of phase change material filling, the exposed portion of the infrared reflective layer surface increases, leading to increased radiative heat loss.
[0084] Compare with Example 5 The difference between this comparative example and Example 1 is that no microvalve structure was provided; that is, the upper and lower end faces of the honeycomb core were directly sealed with a seamless PET / Al film. The results showed that although the low-temperature insulation performance was excellent (completely sealed), when the ambient temperature rose to 25°C, the internal heat could not be dissipated, and the heat flux density decreased instead of increasing, thus failing to achieve adaptive heat dissipation.
[0085] Compare with Example 6 The difference between this comparative example and Example 1 lies in the preparation method of the high infrared reflectance layer. Specifically, aluminum silver paste is used instead of vacuum sputtered aluminum layer.
[0086] The vacuum sputtering of the aluminum layer involves placing the honeycomb core substrate into a vacuum chamber, evacuating the chamber with a vacuum pump, introducing argon gas at a flow rate of 300 sccm, turning on the bias power supply at 800V, using high-purity aluminum as the target material, and adjusting the target current to 20A.
[0087] The specific steps for applying aluminum silver paste are as follows: mix floating aluminum silver paste with high flash point naphtha solvent at a mass ratio of 1:1, scrape it onto the honeycomb core, pre-bake at 70°C for 5 minutes, and then cure at 120°C for 15 minutes to harden the coating.
[0088] The aluminum layer obtained by using aluminum silver paste has an uneven thickness and an infrared reflectivity of only 82%. This leads to enhanced radiative heat transfer inside the honeycomb core and a decrease in overall insulation performance.
[0089] The two control samples from Comparative Example 1 and the material prepared in Example 1 of this invention were respectively coated onto a 75°C hot water pipe of the same specification, and the heat dissipation performance was tested under different ambient temperatures. The test ambient temperatures were -20°C, 0°C, 10°C and 25°C, the wind speed was 0.5 m / s, and the heat flux density and the outer surface temperature of the pipe were recorded. The results are shown in Table 1.
[0090] Table 1. Comparison of heat dissipation performance of different insulation materials at different ambient temperatures
[0091] As shown in Table 1, VIP exhibits excellent thermal insulation performance at low temperatures, but its heat dissipation capacity is insufficient at high temperatures. The low outer surface temperature of the pipe hinders effective heat dissipation, potentially leading to overheating in summer. PUR material's thermal conductivity remains largely unchanged with temperature, resulting in significant heat loss at low temperatures and limited heat dissipation at high temperatures. The material of this invention exhibits a heat flux density of 23 W / m² at low temperatures (-20℃), demonstrating good thermal insulation. As the ambient temperature rises, its heat flux density gradually increases, reaching 72 W / m² at 25℃, significantly enhancing its heat dissipation capacity. This intelligent adaptive adjustment effectively balances the needs for thermal insulation in winter and heat dissipation in summer, and the entire process requires no external energy consumption, showcasing significant technological advantages.
[0092] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.
Claims
1. A variable vacuum honeycomb felt insulation material, characterized in that, The following layers are stacked sequentially from the side furthest from the heat source to the side closest to the heat source: a protective / weather-resistant layer, an infrared transparent spacer layer, a thermochromic-radiation layer, a variable vacuum honeycomb core, and an inner surface sealing layer. The variable vacuum honeycomb core is composed of multiple honeycomb cells, and the inner surface of the honeycomb cells is sequentially covered with a high infrared reflective layer and a composite material; the raw materials of the composite material include phase change material microcapsules with glass transition temperatures of -5 to 5℃ and shape memory polyurethane prepolymer. On the upper and lower end faces of the honeycomb cells, a PET / Al composite valve membrane with micro-valve distribution is adhered.
2. The variable vacuum honeycomb felt insulation material according to claim 1, characterized in that, The phase change material microcapsules are hexadecane microcapsules with a phase change point of 0°C, and / or the mass of the phase change material microcapsules accounts for 30-50% of the composite material.
3. The variable vacuum honeycomb felt insulation material according to claim 1, characterized in that, The phase change material microcapsules are eutectic phase change materials of n-pentadecane / n-heptadecane with a phase change point of -5℃ to 5℃, and the mass ratio of n-pentadecane to n-heptadecane is 55-65:35-45. And / or the preparation method of the shape memory polyurethane prepolymer includes: vacuum dehydrating polycaprolactone diol at 100°C for 2 hours, cooling it to 75-85°C, and then adding 4,4 , - Diphenylmethane diisocyanate, with a molar ratio of isocyanate groups to hydroxyl groups of 1.05, reacts at 75-85℃ for 1-3 hours, then 1,4-butanediol is added, stirred for 1-5 minutes, vacuum degassing for 2-10 minutes, and poured into a preheated mold. It is first cured at 55-65℃ for 10-15 hours, and then vulcanized at room temperature for 4-8 days to synthesize the product.
4. The variable vacuum honeycomb felt insulation material according to claim 1, characterized in that, The honeycomb cells are regular hexagonal; And / or, the preparation of the honeycomb cells includes: using aramid-mica paper, impregnating it with 20wt% phenolic resin, curing it at 170-190℃ for 1-5 minutes to make prepreg paper; molding and folding the prepreg paper into a regular hexagonal honeycomb core blank with a side length of 3-5mm and a height of 9-11mm to obtain the honeycomb core blank.
5. The variable vacuum honeycomb felt insulation material according to claim 1, characterized in that, The micro-valve is a cross-shaped micro-slit formed by laser ablation on the PET / Al composite valve membrane. The arm length of the micro-slit is 20-40µm and the dot spacing is 0.5-0.9mm. The high infrared reflectivity layer is a vacuum sputtered aluminum layer with a thickness of 70-90nm and an infrared reflectivity of ≥94%.
6. The variable vacuum honeycomb felt insulation material according to claim 1, characterized in that, The fabrication of the variable vacuum honeycomb core includes the following steps: S1: Vacuum sputtering aluminum layer on the inner surface of the honeycomb hole wall is used as a high infrared reflective layer; S2: Mix phase change material microcapsules with shape memory polyurethane prepolymer to prepare composite coating slurry. Apply the composite coating slurry to the high infrared reflective layer by scraping method, and dry and cure to obtain honeycomb core. S3: Laser processing of a cross-shaped micro-valve on the valve diaphragm; S4: The valve diaphragm with micro-valve is hot-pressed and bonded to the upper and lower end faces of the honeycomb core obtained in step S2 to obtain a variable vacuum honeycomb core. In S2, the coating amount on one side is 23-27 g / m². 2 The drying temperature is 75-90℃, and the drying time is 1-5 minutes; In S3, a heat-sealing adhesive is pre-coated on one side of the valve diaphragm, and a CO2 laser with a power of 8-12W and a pulse width of 0.1-0.3ms is used to ablate the PET / Al film to form a cross-shaped micro-slit array. In S4, the hot pressing is performed at 120-140℃ and 0.4-0.6MPa pressure for 0.5-2s.
7. The variable vacuum honeycomb felt insulation material according to claim 1, characterized in that, The protective / weather-resistant layer is a PET film with a thickness of 40-60µm; And / or the infrared transparent spacer layer is made of porous polyethylene film with an average pore size of 4-6µm, a porosity of 60%, and a thickness of 90-110µm; The thermochromic-radiation layer is a 20-40µm composite coating, and the raw materials of the composite coating include vanadium dioxide composite microcapsules and methylated melamine-formaldehyde resin in a mass ratio of 1:2-4. And / or the inner surface sealing layer is a 22-27µm thick high-temperature resistant silicone film.
8. The variable vacuum honeycomb felt insulation material according to claim 7, characterized in that, The variable vacuum honeycomb felt insulation material is surrounded by circumferentially woven PET-spandex elastic straps. And / or the preparation of the vanadium dioxide microcapsules includes: (1) Vanadium dioxide nanoparticles were dispersed in an ethanol solution containing silane coupling agent KH-570 and stirred at 55-65℃ for 3-5h to modify the surface, thereby obtaining modified vanadium dioxide. (2) Mix melamine and formaldehyde solution at a molar ratio of 1:2-4, adjust the pH to 8-9 with triethanolamine, and react at 65-75℃ for 20-40 min to obtain melamine resin prepolymer; (3) Disperse the modified vanadium dioxide in deionized water and sonicate for 20-40 min to obtain a vanadium dioxide dispersion; slowly add the melamine resin prepolymer to the vanadium dioxide dispersion, adjust the pH to 4-5 with citric acid, stir at 65-75℃ for 2 h, filter, wash and dry to obtain vanadium dioxide composite microcapsules. The composite coating preparation method is as follows: vanadium dioxide composite microcapsules are mixed with methylated melamine-formaldehyde resin at a mass ratio of 1:3, an appropriate amount of deionized water is added and the mixture is ground and dispersed for 30 minutes, then 1-2% of the mass of MF resin with a blocked p-toluenesulfonic acid curing agent is added, the mixture is stirred evenly and then coated onto a PE film. The coating is pre-cured at 80°C for 30 minutes and then cured at 120°C for 30 minutes to obtain the final product.
9. A method for preparing the variable vacuum honeycomb felt insulation material according to any one of claims 1-8, characterized in that, Includes the following steps: (1) The protective / weather-resistant layer, infrared transparent spacer layer, and thermochromic-radiation layer are stacked on the side of the variable vacuum honeycomb core away from the heat source in sequence. The inner surface sealing layer is attached to the side of the variable vacuum honeycomb core close to the heat source to obtain the laminated material. The laminated material is heat-sealed around its perimeter, and an air extraction port is reserved to obtain the overall component. (2) Heat the entire assembly to 110-130°C, evacuate through the air extraction port until the internal air pressure is below 100Pa, and seal the air extraction port under vacuum. (3) Cool the entire assembly after sealing the air extraction port to a temperature of -15~-5℃ and set for 20-50 minutes; (4) The circumferential elastic band is then tied around the periphery to obtain the desired result; In step (1), the four sides of the laminated material are heat-sealed with PET / Al composite foil with a width of 4-6mm, and a φ2-4mm air extraction port is reserved. In step (2), under the condition of maintaining vacuum, the evacuation port is melted and sealed with heat sealing pliers.
10. The application of the variable vacuum honeycomb felt insulation material according to any one of claims 1-8 or the variable vacuum honeycomb felt insulation material prepared by the preparation method according to claim 9 in 60-90℃ heat source equipment, special functional clothing, 60-120℃ industrial low temperature steam pipelines, building exterior wall insulation systems in severely cold regions, cold chain transportation equipment, new energy battery thermal management, or solar water heater collector tube insulation.
Citation Information
Patent Citations
Low-thermal-conductivity phase-change energy-storage thermal-insulation board as well as preparation method and application thereof
CN113524802A
Polyurethane composite board based on phase change heat preservation and manufacturing method thereof
CN116811398A